Effect of COVID-19 with or without acute kidney injury on inpatient mortality in England: a national observational study using administrative data - Nitin V Kolhe; Maarten Taal; Richard Fluck (BMJ Open)
Objectives To evaluate hospital outcomes and their predictors during the pandemic for patients with and without COVID-19, stratified by the presence of acute kidney injury (AKI).Design Retrospective observation study using the Hospital Episodes Statistics database for England.Participants 2 385 337 unique hospital admissions of adult patients from March 2020 to March 2021 in England.Main outcome measures COVID-19 cases were identified by the International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) code of U07.1. Patients with suspected COVID-19 (U07.2 code) and patients with end-stage kidney disease on chronic dialysis (N18.6 and Z99.2) were excluded. AKI cases were identified by the ICD10 code. Patients were categorised into four groups based on COVID-19 and AKI diagnoses: Group 1—neither; Group 2—COVID-19 only; Group 3—AKI only; Group 4—both. A multivariable logistic regression model was created with in-hospital mortality as the outcome, including diagnostic groups, demographics, admission methods, comorbidity severity, deprivation index and intensive therapy unit (ITU) admission.Results Among 2 385 337 admissions involving 663 628 patients, 856 544 had AKI (N17 codes) and 1 528 793 did not. Among patients without AKI, there were 1,008,774 admissions among 133,988 individuals without COVID-19 (Group 1) and 520,019 admissions among 256,037 individuals with COVID-19 (Group 2). Among patients with AKI, there were 630,342 admissions among 218,270 individuals without COVID-19 (Group 3) and 226,202 admissions among 55,333 individuals with COVID-19 (Group 4). Patients in group 4 were older (75.4 ± 13.8 years) and had greater length of stay (17.1 ± 17 days) than all other groups. They also had and had a greater proportion of males, ethnic minorities and comorbidities than other groups. Mortality was highest in Group 4 (28.7%) and lowest in Group 1 (1.1%). The increased risk of death persisted after controlling for multiple baseline factors (OR for death vs Group 1: Group 4—22.28, Group 2—9.67, Group 3—6.44). ITU admission was least required in Group 1 (1.2%) and most in Group 4 (10.9%), with mortality at 4.8% versus 47.8%, respectively.Conclusions Patients with COVID-19 and AKI have a high risk of mortality and should be recognised early and provided with optimal support. Planning for future pandemics should ensure adequate critical care and acute dialysis capacity.Trial registration number NCT04579562.